2012
DOI: 10.1103/physreve.86.056711
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic correlations in multiparticle collision dynamics fluids

Abstract: The emergent fluctuating hydrodynamics of the multiparticle collision dynamics (MPC) approach, a particlebased mesoscale simulation technique for fluid dynamics, is analyzed theoretically and numerically. We focus on the stochastic rotation dynamics implementation of the MPC method. The fluid is characterized by its longitudinal and transverse velocity correlation functions in Fourier space and velocity autocorrelation functions in real space. Particular attention is paid to the role of sound, which leads to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
169
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(176 citation statements)
references
References 75 publications
7
169
0
Order By: Relevance
“…[24] and references therein). In particular, the hydrodynamic correlations of the MPC fluid have been determined and it has been shown that they agree with the solutions of the fluctuating Landau-Lifshitz NavierStokes equations [25]. Moreover, the hydrodynamic correlations of embedded colloids [26][27][28][29][30][31] and polymers [32] have been calculated.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…[24] and references therein). In particular, the hydrodynamic correlations of the MPC fluid have been determined and it has been shown that they agree with the solutions of the fluctuating Landau-Lifshitz NavierStokes equations [25]. Moreover, the hydrodynamic correlations of embedded colloids [26][27][28][29][30][31] and polymers [32] have been calculated.…”
Section: Introductionmentioning
confidence: 77%
“…(20)- (23) are in order. In the limitγ → 0, we get φ(k, t) → kt and χ(k, t) → k 2 t, and therefore the correlation functions are reduced to the corresponding equilibrium relations [25,33] to O(k 2 ). In the absence of shear, the correlation functions for an isothermal MPC fluid can be obtained for all orders in k; the exact expressions for the velocity autocorrelations are provided in Ref.…”
Section: B Hydrodynamic Correlation Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an appropriate choice of parameters, SRD dynamics capture this hydrodynamic regime (27). Following the approach of Huang et al (36), analysis of the velocity correlations (Fig. S1 in the Supporting Material) demonstrates that SRD parameters appropriate for lipid simulation achieve the low-Re, incompressible regime.…”
Section: Srd Fluid Viscosity and Hydrodynamic Propertiesmentioning
confidence: 99%
“…MPC simulations, previously used to study hydrodynamic correlations [44][45][46] and the fluctuation-dissipation theorem [47] in fluid dynamics, have the advantage of being carried out in a gaslike model, where the typical excitations yielding large density fluctuations typical of lattice models can be neglected.…”
Section: Introductionmentioning
confidence: 99%